PROBLEMS IN IMPLEMENTING AND OBSERVING THE LAW OF WAR IN THE CENTRAL CAUCASUS - MAKILI-ALIEV, Kamal (CENTRAL ASIA AND THE CAUCASUS, 2006)
The breakup of the U.S.S.R. was a process marked by conflicts for all countries of the Central Caucasus. Many experts have tried to define these conflicts as ethnic, regional, separatist, national liberation, terrorist, etc. But they are probably agreed on one point: all these conflicts are rooted in the geopolitical struggle for spheres of influence. The nature of the conflict in each particular case was determined by the “scenario” of its emergence and development. That is why, despite common features, there are significant distinctions between the conflicts in Georgia and Azerbaijan. First of all, the conflicts in Geogia are formally internal, being initiated by the “home-grown” separatist forces of Abkhazia and South Ossetia, whereas the Nagorno-Karabakh conflict is an interstate conflict, which broke out as a result of Armenia’s aggression against Azerbaijan and was carried out under cover of the separatist ideas of some circles in Nagorno-Karabakh. The conflicts in Georgia did not entail an invasion of the country by foreign armed forces, whereas the Nagorno-Karabakh conflict has resulted in the occupation of 20 percent of Azerbaijan’s territory by the armed forces of Armenia. Consequently, there are conflicts in two of the three Central Caucasian states (Georgia and Azerbaijan), while the third state (Armenia) is involved in one of these conflicts in the role of an aggressor occupying Azerbaijani territories.1 In light of the above, the problems of implementation and observance of inter-national humanitarian law (IHL) are of particular importance to the region.